From Faith to Faith John Wesley's Covenant Theology and the Way of Salvation. - Rodes, Stanley J. (Cambridge : James Clarke & Co, 2014)
The very title of this volume makes a claim and extends an invitation. Simply put, the claim is this: John Wesley was an adherent of covenant theology. Consequently, a proper understanding of his theological thought - and of his soteriology in particular - is impossible apart from accounting for the influence of covenant theology on him. The invitation then, is to investigate Wesley''s thought in light of this claim.Having started his research simply as an investigation into a rather curious distinction Wesley made among those to whom he gave spiritual counsel (some people, he said, have ""the.
8. The Holy Spirit and the Salvific Perfection of the Covenant of Grace9. "From Faith to Faith": John Wesley's Pastoral Application of Covenant Theology; 10. Epilogue; Bibliography; Back cover
Includes bibliographical references.
Master record variable field(s) change: 072
Keywords: Wesley, John, -- 1703-1791.; Wesley, John, -- 1703-1791.; Covenant theology -- History of doctrines -- 18th century; RELIGION / Christian Theology / Systematic; RELIGION / Christianity / General; Covenant theology -- History of doctrines; RELIGION / Christian Theology / Soteriology; 1700 - 1799; Electronic books